Plutonium and cesium baseline concentrations in seawater from northern Arabian Gulf. Issue 1 (15th July 2017) - Uddin, S.; Aba, A.; Behbehani, M.; Al-Ghadban, A.N.; Al-Zekri, W.; Al-Shammari, H.
Abstract: The Arabian Gulf is a semi-enclosed water body that has witnessed accelerated anthropogenic activity, in terms of commissioning of nuclear power plants, desalination facilities, oil refineries and extensive coastal development. Furthermore, three wars during the past three decades is a potential worry. This study presents the first plutonium baseline in seawater from the Northern Arabian Gulf. The 239 + 240 Pu concentrations in seawater vary, between 2.9 and 4.9 mBq m − 3, a range that is comparable to other water masses at this latitude. The 238 Pu ranged between 0.04 and 0.05 mBq m − 3 and the 137 Cs concentration between 1.04 and 1.18 Bq m − 3 . The ratio of 238 Pu/ 239 + 240 Pu at all eight sampling stations was 0.01, while the ratio of 239 + 240 Pu/ 137 Cs varied between 0.01 and 0.02. The presence of 137 Cs and 239 + 240 Pu in seawater from this region can mainly be attributed to the global atmospheric deposition and fluvial transport. The seawater concentration of 239 + 240 Pu is five order of magnitude lower than bottom sediments in the area. Highlights: The study reports baseline concentrations of 238 Pu, 239 + 240 Pu, and 137 Cs in seawater. Knowledge of radionuclide concentrations in seawater is critical to avoid producing contaminated freshwater by desalination. With nuclear plants being constructed in Gulf, baseline information on Pu in coastal seawater is important.